A mimic of nasopharynx carcinoma turned out to be primary nasopharynx tuberculosis - Chandrashekaran, Sivanes; Abd Ghani, Mohd Syukra bin (International Journal of Research in Medical Sciences, 2018)
Nasopharyngeal tuberculosis is indeed a rare manifestation of extrapulmonary tuberculosis. The general symptoms of nasopharyngeal tuberculosis are nasal obstruction, neck mass, epitaxis, rhinorrhoea, otalgia and hearing loss. Constitutional symptoms may present in almost 12-30% of nasopharyngeal tuberculosis cases, hence it often disguise as nasopharyngeal carcinoma in patients. Apart from that, most cases of nasopharyngeal tuberculosis usually occur with combined active pulmonary tuberculosis or systemic infection. Hereby presenting a case of nasopharyngeal tuberculosis in a lady who is otherwise healthy presented with neck mass for duration of two months with no obstructive symptoms. Upon proceeding with rigid nasal endoscopy, obliteration of fossa of rossenmuller was noted and biopsy confirmed tuberculosis. Patient was immediately started on antituberculosis therapy. Upon subsequent follow ups, resolution of the neck mass was noted. Hence, it is crucial to have a high index of suspiciousness to rule out nasopharyngeal tuberculosis as this is a curable disease and failure to do so can pave way for the deathly pathogen to disseminate in its host and cause mortality.